The effect of internal control, integrated report and external assurance on SOE’s market value: the moderating role of board representation - Monika Kussetya Ciptani; Arinjani Novita Sari (Diponegoro International Journal of Business, 2024)
This research was motivated by the expansion of businesses and enthusiasm of market participants regarding the fluctuating value of the market itself. The goal of this study is to test, analyze, and find empirical evidence of the impact of internal control, integrated report, and external assurance on market value, with board representation serving as a moderator. The sample of this study were collected using purposive sampling method from Indonesia state owned enterprises (SOEs) from 2017 to 2021 which listed on the Indonesia Stock Exchange. Analysis using multiple linear regression analysis finds that internal control has a negative effect and external assurance has a positive effect that significant on market value, while the integrated report has no effect on market value. Board representation as a moderation variable weakens the negative relationship between internal control and market value, but it cannot strengthen the positive relationship between external assurance and market value, and it has no effect on the relationship between integrated report and market value.